Phenethyl Isothiocyanate Enhances the Cytotoxic Effects of PARP Inhibitors in High-Grade Serous Ovarian Cancer Cells - Jia, Yaxun; Wang, Min; Sang, Xiaolin; Liu, Pixu; Gao, Jingchun; Jiang, Kui; Cheng, Hailing (Frontiers in Oncology, 2022)
While PARP inhibitor (PARPi) therapies have shown promising results in the treatment of high-grade serous ovarian cancer (HGSOC) harboring homologous recombination deficiencies, primary resistance to PARPi frequently occurs and even initial responders may eventually become resistant. Therefore, the development of novel effective combinatorial strategies to treat HGSOC is urgently needed. Here, we report that H2O2-induced oxidative stress sensitized HGSOC cells to PARPi BMN 673. Furthermore, Phenethyl isothiocyanate (PEITC) as a ROS-inducing agent significantly enhanced the cytotoxic effects of BMN 673. Mechanistically, combined use of PEITC and BMN 673 resulted in ROS overproduction and accumulation, enhanced DNA damage, G2/M arrest and apoptosis, all of which were significantly reversed by the ROS scavenger N-Acetyl-L-cysteine. We also showed that while PEITC did not further enhance the ability of BMN 673 on PARP1 trapping in HGSOC cells, the therapeutic effects of the PEITC/BMN 673 combination were at least in part dependent on the presence of PARP1. Importantly, the PEITC/BMN 673 combination potently abrogated the growth of HGSOC tumor spheroids and patient-derived organoid models of HGSOC and cervical cancer. Our findings provide a basis for further investigation of the utility of PARPi combination regimen in HGSOC and cervical cancer through ROS-mediated mechanisms.